1989
DOI: 10.1111/j.1745-9125.1989.tb01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Race, Homicide Severity, and Application of the Death Penalty: A Consideration of the Barnett Scale*

Abstract: This study uses the Barnett scale of homicide severity to analyze the capital sentencing process in Kentucky. In his analysis of Georgia cases, Barnett found that whites were disproportionately the victims of homicides that the scale considered as most serious. This conclusion was cited as an explanation for racial disparity in capital sentencing. When the scale is applied to Kentucky data and the level of seriousness of the murder is controlled, however, we Jind that prosecutors were more likely to seek the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…It appeared, in fact, that within-race African American homicides were "treated as less aggravating deaths" (p. 453). Keil and Vito (1989) concurred: Similar racial offender-victim patterns were found in capital homicide cases in Kentucky. Prosecutors were more likely to seek the death penalty for, and juries more likely to sentence to death, African American offenders who killed whites.…”
Section: Previous Literature On Race and Criminal Justice Disparitysupporting
confidence: 54%
See 1 more Smart Citation
“…It appeared, in fact, that within-race African American homicides were "treated as less aggravating deaths" (p. 453). Keil and Vito (1989) concurred: Similar racial offender-victim patterns were found in capital homicide cases in Kentucky. Prosecutors were more likely to seek the death penalty for, and juries more likely to sentence to death, African American offenders who killed whites.…”
Section: Previous Literature On Race and Criminal Justice Disparitysupporting
confidence: 54%
“…Use of both interracial categories seemed to overcome these problems, however. This resulted in Prior literature has considered the influence on sentencing of such factors as offense charge, bail status, type of counsel, indigence, employment status, occupational prestige, judicial ideology, number of victims, offense type, specific offense, plea, judge's gender, relationship to the victim, and offender's and victim's ages (e.g., Farrell and Swigert 1986;Pruitt and Wilson 1983;Petersilia 1985;Radelet and Pierce 1985;Miller et al 1986;Keil and Vito 1989;Spohn and Cederblom 1991). Unfortunately, many of these variables were either unavailable or incompletely recorded, rendering them of little or no utility for this study.…”
Section: Methodsmentioning
confidence: 99%
“…It stands in contrast to the importance attached to the justification for punishment (Matravers 1999) and the political controversies generated by the existence of capital punishment. It also stands in stark contrast to the many empirical studies, which have demonstrated how racial and social discrimination influences the imposition of the death sentence particularly in the US, and the many studies addressing the alleged deterrent effect of capital punishment (see, for example, Keil and Vito (1989), Peterson and Bailey (1991), Beiley (1998) and the many studies reviewed in Hood (1998;). At the cross-national level, there exist only very few analyses by criminologists (Killias 1986;Wiechman, Kendall and Bae 1990) and sociologists (Neapolitan 2001;Greenberg and West 2003).…”
Section: Death Penaltymentioning
confidence: 87%
“…It stands in contrast to the importance attached to the justification for punishment (Matravers 1999) and the political controversies generated by the existence of capital punishment. It also stands in stark contrast to the many empirical studies, which have demonstrated how racial and social discrimination influences the imposition of the death sentence particularly in the US, and the many studies addressing the alleged deterrent effect of capital punishment (see, for example, Keil and Vito (1989), Peterson and Bailey (1991), Bailey (1998) and the many studies reviewed in Hood (1998;). At the cross-national level, there exist only very few analyses by criminologists (Killias 1986;Wiechman et al 1990) and sociologists (Neapolitan 2001;Greenberg and West 2003).…”
mentioning
confidence: 79%